GCN5 Dependence of Chromatin Remodeling and Transcriptional Activation by the GAL4 and VP16 Activation Domains in Budding Yeast - Stafford, Grace A. (American Society for Microbiology, 2001)
Chromatin-modifying enzymes such as the histone acetyltransferase GCN5 can contribute to transcriptional activation at steps subsequent to the initial binding of transcriptional activators. However, few studies have directly examined dependence of chromatin remodeling in vivo on GCN5 or other acetyltransferases, and none have examined remodeling via nucleosomal activator binding sites. In this study, we have monitored chromatin perturbation via nucleosomal binding sites in the yeast episome TALS by GAL4 derivatives in GCN5(+) and gcn5Δ yeast cells. The strong activator GAL4 shows no dependence on GCN5 for remodeling TALS chromatin, whereas GAL4-estrogen receptor-VP16 shows substantial, albeit not complete, GCN5 dependence. Mini-GAL4 derivatives having weakened interactions with TATA-binding protein and TFIIB exhibit a strong dependence on GCN5 for both transcriptional activation and TALS remodeling not seen for native GAL4. These results indicate that GCN5 can contribute to chromatin remodeling at activator binding sites and that dependence on coactivator function for a given activator can vary according to the type and strength of contacts that it makes with other factors. We also found a weaker dependence for chromatin remodeling on SPT7 than on GCN5, indicating that GCN5 can function via pathways independent of the SAGA complex. Finally, we examine dependence on GCN5 and SWI-SNF at two model promoters and find that although these two chromatin-remodeling and/or modification activities may sometimes work together, in other instances they act in complementary fashion.